Identification of Potential Hazards in Occupational Safety and Health Among Rice Milling Workers at UD. Lestari - Mayadilanuari, Aerrosa Murenda; Nurvita, Silvia; Chotimah, Siti Noor; Dewi, Viny Natalia; Kurniawan, Dhieo (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2024)
Occupational health and safety (OHS) is crucial for safeguarding workers' well-being and preventing workplace accidents and diseases. This study explores OHS hazards at UD Lestari, an informal sector rice milling operation in Semarang City, Indonesia. The research employed a descriptive qualitative approach, conducting interviews, observation, and measurements from April to May 2024. The aim of this study was to identify various OHS hazards present in UD. Lestari's rice milling operations. This research found that all respondents experienced respiratory problems (100%) and 3 people (50%) experienced hearing problems, attributed to inadequate use of Personal Protective Equipment (PPE) and smoking habits. Dust levels inside the production area exceeded permissible limits (8.04 mg/m3), posing risks of respiratory diseases. Similarly, noise levels surpassed recommended thresholds (93.26 dB), increasing the likelihood of hearing loss. This study contributes valuable insights into enhancing workplace safety and underscores the importance of ongoing efforts to safeguard worker health in informal sector industries. Future research should explore additional factors influencing OHS outcomes to further enhance workplace safety practices and employee well-being.